GAMBARAN HISTOLOGIK KORTEKS SEREBRUM CODOT (Rousettus sp.) DENGAN PEWARNAAN CRESYL ECHT VIOLET - , SITI KHOMARIYAH; , Dr. drh. Tri Wahyu Pangestiningsih ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia is a megabiodiversity country which has more than 200 species of bats, one of them is codot (Rousettussp). Codot is able to identify nearby objects with echolocation. In identifying surrounding objects, process of remembering is very important. Part of the brain that play a role in the regulation of memory is cerebral cortex. This study aims to determine the cerebral cortex histology of codot. Codot from Central Java were used as a sample. The cerebrum blocked in paraffin, sliced in 12 μm thickness and stained using Cresyl Echt Violet. The results of staining was observed with a microscope. The examined area were hippocampal formation as a representative of archicortex, cingulate gyrus as representative of paleocortex and parietal lobe as a representative of neocortex areas. Those areas were photographed and analyzed using Microsoft Excel software , CorelDraw X6 , Adobe Photoshop CS4 and Optilab Raster Image . The results showed that the codot hippocampal formation is composed of dentate gyrus, hippocampus proper and subiculum. Neurons at dentate gyrus are small multipolar in shape with 5.53 ± 0.77 μm in diameter and 101 ± 40.92 cells / 30000 μm2 in density. Pyramidal stratum of hippocampal proper is divided into three areas, cornu amonis (CA)1, CA2 and CA3 with pyramidal cell diameter are respectively 10,30 ± 1,42 μm, 16,54 ± 1,17 μm and 14,24 ± 1,92 μm, and the cell density are respectively 33 ± 7,96 cells / 30000 μm2, 44 ± 5,68 cells / 30000 μm2 and 36 ± 13,06 cells / 30000 μm2. Subiculum composed of pyramidal cells that are divided into the outer layer and inner layer with cell diameter are respectively 8,66 ± 1,06 μm and 13,52 ± 1,93 μm and cell density are respectively 22 ± 4,50 cells / 30000 μm2 and 20 ± 3,95 cells / 30000 μm2. Cingulat gyrus and parietal lobe is composed of molecular, external granular, external pyramidal, internal granular, interna pyramidal and multiform stratums. The conclusion of this study is hippocampal formation as a representative of archicortex composed of dentate gyrus, hippocampus proper and subiculum, cingulat gyrus as a representative of paleocortex and parietal lobe as a representative of neocortex is composed of six stratums. Cells in each stratum of parietal lobe arranged more regularly than cingulate gyrus.